Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada CV Sumber Rejeki Tehnik Sukses: The Effect of Service Quality and Product Quality on Customer Satisfaction at CV Sumber Rejeki Tehnik Sukses - Ika Khotimah; Henny Armaniah (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Business competition requires companies to maintain the quality of services and products in order to increase customer satisfaction. CV Sumber Rejeki Teknik Sukses which is engaged in repair services and manufacturing machine components using lathe techniques. The purpose of this study is to determine the influence of service quality and product quality on customer satisfaction on CV. A Source of Success Techniques. The research method used is a quantitative method with data collection techniques using observation, questionnaires, interviews, and literature studies. The population in this study was 62 customers, with a sample of 62 respondents. The result of this study is that the quality of service partially does not have a positive and significant effect on customer satisfaction in CV. A Source of Success Techniques. The results were obtained from t calculated -0.820 > from t table 1.2960 with a sig of 0.416 > 0.05. Product quality partially has a positive and significant effect on customer satisfaction in CV. A Source of Success Techniques. The results were obtained from t calculation 9,130 > from t table 1.2960 with sig 0.000 < 0.05. Simultaneously, the quality of service and product quality had a significant effect on customer satisfaction in CV Sumber Rejeki Teknik Sukses. The results were obtained from the value of f calculated 420,222 > from f table 3.15 and significant of 0.000 < 0.05